The effect of a 3×3 full diallel crossing on the growth and reproductive performance of three rabbit breeds reared within the coastal savannah agro-ecological zone in Ghana - Opoku-Mensah, Louis (University of Cape Coast, 2017)
Data on a full diallel cross involving three rabbit breeds and its effects on some growth and reproductive traits were studied. Data on two thousand and thirteen (2,013) rabbits comprising eight hundred and five (805) purebred bunnies kindled in 60 litters and one thousand, two hundred and five (1,205) crossbred bunnies from 86 litters bred from 2010 to 2014 in five parities were first corrected for the fixed effects of sex, season of kindling and the does‘ age using the least significant differences (lsd) before the analysis was run using the Generalised Linear Model. Of the three breeds, the Chinchilla showed superior performance in both the reproductive and growth performance while the BV X CH crossbred showed superior performance in most of the economic traits that were assessed compared to the other crosses. The BV X NZ and NZ X CH crossbreds recorded significantly (p = <0.05) higher litter size at birth (6.8±0.1) and at weaning (6.9±0.1) respectively. The heterotic effects of both the main and reciprocal crosses were quite desirable for most of the economic traits. Notable among them was the age at sexual maturity, kindling interval and mortalities which recorded varying levels of negative heterosis. The reciprocal crosses exhibited some level of superiority in the growth traits (bunny weight at birth and the post-weaning growth rate) that recorded positive heterosis. The Chinchilla and BV X CH crossbred comparatively exhibited a higher level of superiority in the general and specific combining abilities in a number of the economic traits that recorded significant differences. The positive heterotic effects encourage the application of crossbreeding schemes in rabbit production for improved productivity within the coastal savannah agro-ecological zone of Ghana.
xiii,175p:, ill.
Keywords: Diallel crossing Heterosis General combining ability Specific combining ability Crossbreeding Reproductive Breed complementarity Crossbred Agro-ecological